Legal Problems in the Enforcement of Final and Binding Judicial Decisions: A Jurisprudential Analysis of the Silfester Matutina Conviction Case from an Indonesian Law Enforcement Perspective (Legtimacy: Journal of Law and Islamic Law, 2025)
The enforcement of final and binding judicial decisions is essential to uphold legal certainty and the rule of law. However, in Indonesia, significant delays and non-execution of criminal convictions have exposed systemic deficiencies. This study presents a jurisprudential analysis of the Silfester Matutina conviction case where a 1.5-year prison sentence issued by the Supreme Court in 2019 remained unexecuted through August 2025 to examine the legal and institutional factors causing enforcement failure. Employing a normative juridical approach combined with case study methodology, the research integrates doctrinal analysis of statutes, judicial decisions, and prosecutorial regulations with theoretical frameworks from Legal Positivism, Sociological Jurisprudence, Legal Realism, and Natural Law. Quantitative indicators were applied to assess legal certainty, prosecutorial discretion, public trust impact, and constitutional compliance. Findings reveal a six-year enforcement gap, a 75% decline in legal certainty, and excessive prosecutorial discretion (95% vs. international benchmark of 35%), confirming the abuse of discretionary power and the erosion of institutional legitimacy. Comparative analysis with European best practices highlights the need for specialized enforcement bodies and mandatory execution timelines. The study concludes with policy recommendations for legislative reform, institutional restructuring, and enhanced oversight to restore public trust, ensure timely execution of judgments, and reinforce the deterrent effect of criminal sanctions. Limitations and avenues for future empirical research are also discussed.